From the history of polycystic ovary syndrome - D. A. Kiryushkina (Акушерство, гинекология и репродукция)
Polycystic ovary syndrome (PCOS) is a gynecological disease manifested in polycystic ovarian morphology, oligo/ anovulation, hyperandrogenism, hirsutism, alopecia, and acne. PCOS affects 5–10 % of women of reproductive age. The first histological description of polycystic ovaries was made by Antonio Vallisneri. Then, Kronid Fedorovich Slavyanskiy, for the first time, described the clinical picture of PCOS, and Sergey Kuzmich Lesnoy proposed ovary wedge resection for surgical treatment. Irving Stein and Michael Leventhal studied the PCOS symptom complex and provided the recommendations on its diagnosis and treatment to restore normal menstrual cycle and fertility in such patients.